Circulating Interleukin-6 (but Not Other Immune Mediators) Associates with Criteria for Fried’s Frailty among Very Old Adults - Gilberto Santos Morais Junior; Diego Ignacio Valenzuela Perez; Audrey Cecília Tonet-Furioso; Lucy Gomes; Karla Helena Coelho Vilaça; Vicente Paulo Alves; Clayton Franco Moraes; Otávio Toledo Nóbrega (Journal of Aging Research)
Background and Aim. Frailty is a geriatric condition resulting from physiological changes covering the musculoskeletal, immune, and neuroendocrine systems, leading to a greater inflammatory state. The present research aimed to investigate the association of components of Fried’s frailty (as well as of the phenotype as a whole) with total serum levels of a panel of inflammatory mediators. Methods. One hundred and sixty-one very old patients (aged ≥80 years) devoid of cognitive decline were eligible for analyses. Clinical and biochemical data along with physical and cognitive assessments encompassing dual-energy X-ray scans and hand dynamometry were adopted to investigate frailty criteria, while circulating immune mediators (IFNγ, IL-2, IL-4, IL-6, IL-10, and TNFα) were assessed using high-throughput flow cytometry. Results. Preliminarily, IL-6 correlated positively with waist-to-hip ratio and C-reactive protein and negatively with glycemia. In analyses controlled for these factors, serum levels of IL-6 were comparatively augmented among the very old participants with reduced grip strength (OR = 3.299; 95% CI 1.08–6.09; p=0.032) and among those with slow walk speed (OR = 2.460; 95% CI 1.16–7.05; p=0.022). Conclusions. Our study shows a strong negative correlation of IL-6 levels with Fried’s frailty components of grip strength and walk speed in very old adults, regardless of confounding factors.